AB113. The function of miR-210 in varicocele rats with infertility - Chen, Yegang (Transl Androl Urol, 2016)
OBJECTIVE: To evaluate the function of miR-210 in varicocele rats with infertility. METHODS: Thirty male SD rats (7-week-old) were divided into control group, experimental group and surgical group (10 rats in each group). We operate on abdominal incision, then narrow the left renal vein and ligature the vein between left spermatic vein and the left iliac vein in experimental group and operation group. The control group is exposed as the same as the experimental group, but the vein was not narrowed and ligatured. Eight weeks after modeling, we measure anesthesia spermatic vein diameter and collect the left testis and epididymis fluid. In operation group, we ligature left anesthesia. Four weeks later, we collect the same specimen as the other two groups. RT-PCR was used to test the miR-210. Western blot was used to test the expression of HIF-α. RESULTS: The left spermatic vein diameter, the expression of HIF-α and miR-210 in testis and epididymis fluid in experimental group is larger than in control group. The weight of testis is lower than in control group. In operation group, the left spermatic vein diameter, the expression of HIF-α and miR-210 decreased significantly. HIF-α was positively correlated with miR-210. CONCLUSIONS: Increased level of miR-210 is an important reason of male infertility caused by varicocele. miR-210 can be a predictor of infertility caused by varicocele and a marker of curative effect of operation. Varicocele caused male infertility may through miR-210/HIF-1α pathway.